Characterisation of short fatigue cracks in titanium alloy IMI 834 using X-ray microtomography. (15th October 2015) - Chapman, T.P.; Kareh, K.M.; Knop, M.; Connolley, T.; Lee, P.D.; Azeem, M.A.; Rugg, D.; Lindley, T.C.; Dye, D.
Graphical abstract: Abstract: A first attempt at the three-dimensional evaluation of naturally initiated surface connected and internal fatigue cracks is presented. Fatigue crack initiation and growth in air and vacuum environments have been investigated through X-ray microtomography in air and vacuum environments at elevated temperatures (350 °C), accompanied by post-mortem electron microscopy of the fracture surfaces. In vacuum ( < 10 −5 mbar), multiple internal and surface-connected crack initiation was observed, but only the surface-connected cracks grew. In contrast, fewer cracks formed in air, these were mostly surface-connected and all were observed to grow. In all instances the initiation features were associated with globular primary α . An improved fatigue life was found in vacuum, which was mostly a consequence of delayed initiation, but was also due to slower fatigue crack propagation. The non-propagation of internal cracks was taken to imply that even the good laboratory vacuum obtained here was insufficient to simulate the conditions obtained for an internal crack in a component. The crack shape evolved towards a semi-circular shape a / c = 1 in air during fatigue crack growth, whilst the vacuum cracks remained semi-elliptical ( a / c ≃ 1.4 ). This was taken to imply that oxide-induced crack closure played a role in fatigue crack growth in air.